The potential chemo-preventive roles of Malus domestica against the risk of colorectal cancer: A suggestive insight into clinical application - Köseoğlu, Aygül; Al-Taie, Anmar (Elsevier, 2022)
Biologically active compounds in fruit-derived ingredients, particularly phytochemicals, have significant potential to modulate and mitigate many pathological processes in the development of disease conditions, including cancer. Colorectal cancer (CRC) remains a major public health issue. Nonetheless, prevention is an important step in lowering the rate of mortality from this cancer. Currently, the link between apple consumption and improved health is becoming remarkably evident and is reported to be beneficial for human health. Phytochemicals, such as flavonoids and other polyphenol compounds extensively available in apple fruits, have well-known positive effects on health outcomes and the potential to combat and prevent the development of CRC, including antioxidant, anti-proliferative, and anticarcinogenic effects. This review describes the bioactive compounds derived from apple fruits, particularly the polyphenols and flavonoids, their proposed mechanisms responsible for their bioactive properties and health-promoting attributes that could provide potential chemo-preventive effects against the risk of CRC development. The conclusion of the review provides insights into the potential effects of apple-derived bioactive compounds and proposes the need for more clinical studies in large trials for future strategies regarding the valuable effects of apple phytochemicals, which might be therapeutic candidates in the campaign against CRC.
Keywords: Apple; Chemo-Prevention; Colorectal Cancer; Flavonoids; Malus Domestica; Polyphenols